KOSMOLOGI TATA RUANG PERMUKIMAN TRADISIONAL - I Komang Gede Santhyasa (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2017)
Space creation is an attempt to more accurately accommodate human norms and values both as individuals and group members, in meaningful space. In that space one has an emotional attachment of spiritual and material culture, so space can be made a place by man to realize his existence according to local culture. The Hindu settlement in Dusun Jengglong, Wagir, Malang as a case study is used to explore the creation of a settlement space based on cosmological conceptions (Traditional religious). This research aims to illustrate briefly that this exploration is aimed at better understanding the foundation on which the creation of local spatial expression is evoked by the cultural context. The research method used is explorative with direct observation and interview to see the phenomenon in the field. In this research can be concluded that the process of forming the settlement space in Dusun Jenglong, Wagir, Malang using the traditional conception of religious Hindu Bali culture. This approach as one form of human effort aligns its relationship with living environments to achieve higher (religious) objectivesand in turn creates a supportive environmental quality.